2008
DOI: 10.1128/jvi.00789-08
|View full text |Cite
|
Sign up to set email alerts
|

A Single N-Linked Glycosylation Site in the Japanese Encephalitis Virus prM Protein Is Critical for Cell Type-Specific prM Protein Biogenesis, Virus Particle Release, and Pathogenicity in Mice

Abstract: The prM protein of Japanese encephalitis virus (JEV) contains a single potential N-linked glycosylation site, N 15 -X 16 -T 17 , which is highly conserved among JEV strains and closely related flaviviruses. To investigate the role of this site in JEV replication and pathogenesis, we manipulated the RNA genome by using infectious JEV cDNA to generate three prM mutants (N15A, T17A, and N15A/T17A) with alanine substiting for N 15 and/or T 17 and one mutant with silent point mutations introduced into the nucleotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
79
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 71 publications
(94 reference statements)
9
79
0
Order By: Relevance
“…Though missing the Asn-67 glycosylation site, more virulent strains of WNV are glycosylated at the Asn-153 equivalent site while the envelope proteins of less virulent strains are not [35,36]. Recent studies on Japanese encephalitis virus have shown that a single glycosylation site in the prM protein is critical for viral biogenesis and pathogenicity in mice [37]. Whether the missing glycosylation at position 67 in other flaviviruses is similarly compensated needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Though missing the Asn-67 glycosylation site, more virulent strains of WNV are glycosylated at the Asn-153 equivalent site while the envelope proteins of less virulent strains are not [35,36]. Recent studies on Japanese encephalitis virus have shown that a single glycosylation site in the prM protein is critical for viral biogenesis and pathogenicity in mice [37]. Whether the missing glycosylation at position 67 in other flaviviruses is similarly compensated needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies have indicated important roles of Nglycosylations sites in E protein, but few have focused on prM N-glycosylation. Kim et al (2008) generated a recombinant JEV with N-glycosylation mutant in prM by reverse genetics and they found that JEV secretion was reduced at the stage of virus release, rather than assembly. However, the glycan in prM protein was located in the precursor (pr) section, which was cleaved in the trans-Golgi network during assembly.…”
Section: Discussionmentioning
confidence: 99%
“…N-glycosylation of E protein is known to be important in viral propagation, infectivity, secretion, and neuroinvasion (Beasley et al, 2005;Bryant et al, 2007;Lee et al, 2010;Shirato et al, 2004;Vorndam et al, 1993). However, little attention had been paid to the roles of the N-glycosylation in prM protein until Kim et al (2008) reported that glycosyla-tion of JEV prM protein was associated with viral release and pathogenesis. But how the N-glycan in prM protein affects the viral release and pathogenesis is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, the E protein is not the only site of the viral genome related to phenotype determination of the JEV. A single N-linked glycosylation site in the prM protein of the JEV was documented to be critical for the pathogenicity of the virus in mice (Kim et al, 2008). Factors affecting the genetic diversity of the JEV may be complex and remain to be worked out.…”
Section: Mutations and Evolution Of The Jev In Naturementioning
confidence: 99%